BAGAIMANA PENGARUH SANITASI LINGKUNGAN RUMAH TANGGA DAN PERSONAL HYGIENE IBU BALITA TERHADAP KEJADIAN STUNTING DI PAPUA TENGAH?; ANALISIS DATA SKI 2023 - Wahyuni, Nia Watri; Cheni, Aulia Rahmi; Illahi, Vitratul; Prima, Arif (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Stunting has short-term and long-term impacts. Stunting is caused by many factors. Water, sanitation, and the environment contribute 50% to the causes of stunting. Central Papua is the province with the highest stunting incidence in Indonesia based on SKI 2023 data (38.4%). The purpose of this study was to determine the effect of sanitation and hygiene on stunting in toddlers in Central Papua. The study used a cross-sectional design. Data from SKI 2023 with a sample of 371 (toddler pairs and toddler mothers). The proportion of stunting incidence in Central Papua Province (35.8%). Variables that influence stunting in Central Papua are drinking water sources (OR = 4.079), latrine use (OR = 3.180), waste management (OR = 1.682), CTPS (HWWS) (OR = 1.833). For the government, it is hoped that the results of this study can improve equitable access to sanitation and clean water by increasing collaboration between relevant agencies. For the Health Office, it is hoped that it can optimize the STBM program, increase drinking water monitoring, and improve health promotion on PHBS. Keywords: Stunting, toddlers, sanitation, hygiene